MICROBIAL DIVERSITY IN EXTREME ENVIRONMENTS: A RESOURCE FOR A SUSTAINABLE AGRICULTURE MANAGEMENT - F. Mapelli (Università degli Studi di Milano, 2012)
During the last decades many studies have been undertaken to investigate life in extreme environments, leading to the discovery of novel organisms and novel habitats previously though to be unapproachable for life. Microbes are key players in a number of ecological processes such as mineral dissolution, soil genesis, plant growth promotion (PGP) and bioremediation of polluted sites and they are the main responsibles for element cycles both in conventional and extreme ecosystems. The biotechnological potential of extremophiles is well recognized, and the aim of this PhD project was to give further insight on the possible exploitation of the microbiome naturally adapted to cope with extreme values of one or more environmental parameters to develop sustainable strategies in agriculture and ecosystem management with a particular focus on arid and saline lands. Mineral-microbe interactions have been studied in detail, particularly regarding the importance of bioweathering bacteria in the ambit of soil fertility promotion in arid lands. Specific sites within the Midtre Lovénbreen glacier moraine (Svalbard, Norway), where pyritic rocks were present, hosted an active acidophilic iron-oxidizing bacterial community involved in the bioweathering of pyrite supplied by the rock disaggregation due to winter freezing. A decreased iron concentration and acidification were observed along the wheathered area departing form the pyrite-rich rock, where the oxidation of ferrous iron led to the accumulation of ferric oxy-hydroxides in the above soil. These ferric compounds were linked to the increase of soil physico-chemical properties that in turn determined a higher water holding capacity (WHC) and nutrient content in the surrounding vegetated area, densely colonized by mosses and small vascular plants. At the outer border of the vegetated area, the rest of the moraine hosted typical first colonizer bacteria, mainly belonging to the class Cyanobacteria, that are capable of nitrogen and carbon fixation. Thus, compared to the rest of ...